Evaluación de las interacciones ecológicas Ave-Planta del bosque seco en el sector el Chilco, Cantón Zapotillo y Modelación de Impactos Potenciales - León Hurtado, Nancy Yadira (2015)
The bird-plant interactions are an important environmental service for their role in maintenance, regeneration, pollination and pest control in forests or remnants, both of which are in decline as a result of the impacts of activities anthropogenic. The purpose of the study was to identify the bird - plant interactions present in an area of dry forest and develop a conceptual model to reflect the potential impacts that appear from the disruption of these interactions. The study was conducted at The Chilco of National University of Loja, located in the canton Zapotillo belonging to the province of Loja, were delimited five plots of 50 m2, where are identified the flora and avifauna observed. Were registered 23 families of birds (45 species), highlighting families are: Polioptilidae, Trochilidae, Tyrannidae, Dendrocolaptidae, Psittacidae y Thraupidae. Regarding flora, were found 17 families (27 species) protruding: Bignoniaceae, Fabaceae, Combretaceae, Nyctaginaceae and Erythroxylaceae. The types of interactions recognized were: foraging (insectivorous birds that predominate in abundance and richness), seed dispersal and pollination. With the data obtained and literature review, was developed the conceptual model of the potential impacts that may occur by the alteration of the interactions and their possible effects. The whole of the bird-plant interactions in the forest, guarantee that it will conserve and maintain good health. Also with the development of the conceptual map will allow describe a simplified approach of the structure and behavior of the ecosystem.